Extrapulmonary small cell carcinoma: Multimodality treatment results - (:unkn) unknown (PENSIERO SCIENTIFICO EDITOR, 2003)
Aims and background: Extrapulmonary small cell carcinoma is a distinct entity that can occur in many sites, and it is pathologically similar to small-cell lung cancer. We report the results of a retrospective study of a multimodality treatment of 16 consecutive patients with a diagnosis of extrapulmonary small-cell carcinoma. Methods: Primary tumor site was prostate in 2, gallbladder in 2, uterine cervix in 2, liver in 2, endometrium in 1, epididymis in 1, colon in 1, larynx in 1, breast in 1, and unknown primary tumor in 3 patients. Patients' ages ranged from 19 to 79 years (median, 62). Nine patients had limited and 7 had extensive disease. Histologically, 14 were pure extrapulmonary small-cell carcinoma and 2 were mixed with squamous-cell carcinoma. Results: Curative surgery was attempted in 8 patients. Seven patients received local-regional adjuvant radiotherapy. All patients, except the one with a breast primary, were treated with chemotherapy (mostly platinum-based regimens). Overall survival for all patients was 41% and 11% at 2 and 5 years, respectively (median survival, 14 months). Median survival for patients with limited disease was 25 months compared to 12 months for patients with extensive disease (P = 0.05). Conclusions: Treatment results for extrapulmonary small-cell carcinoma are comparable to those of small-cell carcinomas of the lung. Extent of disease is a significant prognostic factor for survival.
Keywords: chemotherapy; extrapulmonary small cell carcinoma; radiotherapy; LUNG-CANCER; THORACIC RADIOTHERAPY; NEUROENDOCRINE CARCINOMA; CHEMOTHERAPY; THERAPY; BREAST; COMBINATION; CISPLATIN; ESOPHAGUS; ETOPOSIDE